2006
DOI: 10.1136/aim.24.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trigger Point Acupuncture on Chronic Low Back Pain in Elderly Patients – a Sham-Controlled Randomised Trial

Abstract: Introduction There is some evidence for the efficacy of acupuncture, but it remains unclear whether trigger point acupuncture is effective. Our objective was to evaluate the effects of trigger point acupuncture on pain and quality of life in chronic low back pain patients compared with sham acupuncture. Methods Twenty-six consecutive out-patients (17 women, 9 men; age range: 65-91 years) from the Department of Orthopaedic Surgery, Meiji University of Oriental Medicine, with non-radiating low back pain for at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 28 publications
1
95
0
Order By: Relevance
“…For simplicity, each comparison was treated as an individual trial. Trials reported on the following categories of interventions: acupuncture (10 trials) [25,42,73,74,85,95,99,104,106,128], back school (2 trials) [11,28], behavioural (7 trials) [10,21,62,111,130,132,133], electrotherapy (20 trials) [8, 15, 25, 27, 37, 49-51, 54, 57, 63, 69, 76, 77, 89, 94, 107, 122, 137, 143], exercise (10 trials) [29,37,43,48,50,59,67,116,131,136], heatwrap therapy (2 trials) [109,110], insoles (1 trial) [127], magnets (1 trial) [33], massage (1 trial) [116], neuroreflexotherapy (1 trial) [93] [16,117,129]. Trial characteristics are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, each comparison was treated as an individual trial. Trials reported on the following categories of interventions: acupuncture (10 trials) [25,42,73,74,85,95,99,104,106,128], back school (2 trials) [11,28], behavioural (7 trials) [10,21,62,111,130,132,133], electrotherapy (20 trials) [8, 15, 25, 27, 37, 49-51, 54, 57, 63, 69, 76, 77, 89, 94, 107, 122, 137, 143], exercise (10 trials) [29,37,43,48,50,59,67,116,131,136], heatwrap therapy (2 trials) [109,110], insoles (1 trial) [127], magnets (1 trial) [33], massage (1 trial) [116], neuroreflexotherapy (1 trial) [93] [16,117,129]. Trial characteristics are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks for this very helpful note, the faulty citation is very unpleasant for us and we would like to correct this herewith. The correct citations in the section BStatistical analysis^are the ones mentioned above by Inoue [3] and Itou [4].…”
Section: Dear Editormentioning
confidence: 97%
“…In our paper, we present the original sample size calculation as done for the study protocol. This calculation of the number of cases is based on the work of Inoue [3] and Itou [4]. However, according to the pilot character of the study after the end of the intervention phase, we revised our strategy for data analyses based on the large number of measurements over time and the additional 3-month follow-up.…”
Section: Dear Editormentioning
confidence: 99%
“…Further complicating matters, it is unclear what type of methodology should constitute sham acupuncture. Many RCTs have administered to their sham treatment groups a form of minimal acupuncture, involving superficial needle insertion, sometimes at extrameridian sites; as Itoh and colleagues noted, 34 some schools of acupuncture use such techniques in their "real" acupuncture therapy, bringing into question whether any sort of penetrative needling technique could reasonably be considered a "sham. " Itoh et al advocated the use of non-penetrative needling as a sham but, at this time, it is unclear whether variations in sham technique significantly differ in their outcomes.…”
Section: Summary Of Recent Literaturementioning
confidence: 99%